Pengaruh Penggunaan Media Papan Penjumlahan terhadap Hasil Belajar Matematika Kelas IV - Devi Indriani; Muhammad Maki; Erwin Hadi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Elementary school students’ mathematical ability remains relatively low, particularly in understanding basic arithmetic operations such as addition. Many fourth-grade students experience difficulties in solving addition problems because the material is presented abstractly and is not adequately supported by the use of concrete media that can help them visualize the calculation process. This condition results in low learning outcomes, a lack of student confidence in solving mathematics problems, and minimal active participation in learning. Therefore, learning innovations are needed to provide more concrete, engaging, and developmentally appropriate learning experiences for elementary school students. One alternative medium that can be used is the addition board, a manipulative learning medium designed to help students understand the concept of addition through direct counting activities using concrete tools. This study aimed to analyze the effect of using the addition board media on the mathematics learning outcomes of fourth-grade students. The research subjects were 23 fourth-grade students at SDN 18 Cakranegara who participated in learning activities using this media over two cycles of Classroom Action Research (CAR). Each cycle consisted of planning, implementation, observation, and reflection stages. Data were collected through learning outcome tests, student activity observation sheets, and learning documentation. The results showed that the use of the addition board media had a positive impact on improving student learning outcomes. In the pre-cycle, the average student learning outcome was in the fair category, with a mastery percentage of 51%. After the implementation of the addition board media in Cycle I, mastery increased to 70%, and in Cycle II it further increased to 80%. This improvement indicates that the addition board media helps students understand the addition process concretely, creates interactive learning experiences, and enhances students’ motivation and confidence in solving problems. The addition board media also provides varied activities that make learning more engaging, helps students easily understand the steps of addition, enables them to visualize their thinking processes, and encourages more active participation in counting activities. Additionally, this media assists teachers in delivering material and conducting gradual evaluations. Based on the research findings, it can be concluded that the use of the addition board media has a significant effect on improving the mathematics learning outcomes of fourth-grade students and is appropriate for use as an alternative medium in teaching arithmetic operations in elementary schools.